Propping and tunneling: Empirical evidence from Japanese keiretsu - Dow, Sandra; McGuire, Jean (Journal of Banking & Finance, 2009)
We examine the response of horizontal and vertical keiretsu to the changing economic and regulatory climate in Japan from 1987 to 2001. We find evidence of profit tunneling of more weakly affiliated keiretsu firms during strong economic times. We observe propping of weakly aligned firms during recession. Many horizontal keiretsu firms strengthened their degree of adhesion to the horizontal keiretsu in response to increasingly tightened credit conditions post-1991. The motivation behind strengthened affiliation appears primarily linked to the goal of overcoming financial constraints by accessing the internal capital market of the business group.